Implementation of School Culture Management in State Elementary School in the District of Aur Birugo Tigobaleh - Yuhelmi, Yuhelmi; Pohan, Ratna Sari Dewi; Sari, Mezia Kemala (International Journal for Educational and Vocational Studies, 2020)
The formation development and maintenance of school cultural values is very important in order to create honesty, mutual trust, discipline, neat, clean, beautiful and create a harmonious atmosphere so that the formation of student character is good. This study aims to describe the school's cultural planning and implementation. The subjects of this study were principals of primary schools, teachers and students in primary schools in the Aur Birugo Tigobaleh district. Data collection techniques in this study were carried out by means of observation, interviews and documentation. Data analysis techniques use techniques developed by Miles and Huberman (1996). The findings of this study include: (1) school cultural planning is not planned according to MoNE standards; (2) the implementation of school culture is implemented by every school member but it does not yet refer to the correct guidelines. For this reason, it is recommended that schools make plans and implement correctly according to applicable guidelines.